Students Leadership and School Effectiveness in Public Secondary Schools in Jos South Local Government Area of Plateau State - Shittu Lukman Olayinka; Muhammad Ridwan (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2025)
This study students leadership and school effectiveness in public secondary schools in Jos South Local Government Area of Plateau State. The study was guided by five objectives and answered five corresponding research questions four null hypothesis were also tested at 0.05 level of significance. Extensive literature was reviewed. The research design employed was a survey research design specifically cross-sectional survey. The population of this study consisted of all 20 registered public secondary schools in Jos South LGA, Plateau State, with a total of 2,041 SS II students and 20 SS II form teachers, one from each school. The researcher used a sample size of 210 participants, comprising both students and teachers selected from 10 public schools, with 20 SS II students drawn from each school and one SS II form teacher from each selected school. Sample of students were drawn using simple random sampling while form teachers were selected using purposive sampling. the researcher used two questionnaires one for the students and one for the teachers titled “Students Leadership and School Effectiveness Questionnaire for Students’’ (SLSEQS) and Students Leadership and School Effectiveness Teachers Questionnaire’’ (SLSETQ) for both students and teachers respectively. Both questionnaires were subjected to content validity by experts. Internal consistency reliability type was established for both through PPMC at 0.78 and 0.81 for students are teachers questionnaire respectively. The data collected was analysed using descriptive and inferential statistics. The study revealed among other things that the functions of different student leaders, including library prefects, assembly prefects, labour prefects, and sports prefects, were found to influence various aspects of school administration and student engagement. The study also recommended among other things that, school authorities should provide structured training for student leaders to enhance their leadership skills and effectiveness in school administration.